STUDY ON THE PERFORMANCE OF SOME PARAMETRIC PROPORTIONAL HAZARD MODELS AND SEMI-PARAMETRIC MODEL IN THE ANALYSIS OF BREAST CANCER DATA (FUDMA JOURNAL OF SCIENCES, 2023)
A study is conducted on medical records of 416 breast cancer patients. Analysis was performed using the R software version R3.6.3, and the level of significance was set at 0.05. The work employed three models which were based on Exponential, Weibull and Cox Regression models. The Weibull proportional model (AIC=1959.038) was the most appropriate model among the considered models, based on the Akaike information criterion (AIC).  Results of the best fitted model showed that the survival time of breast cancer patients is significantly affected by age, age at diagnosis, and treatment taken at 95%.
Keywords: Semi-Parametric Model; Parametric Models; AIC; Breast Cancer